Cardioprotective effects of the proline‐rich oligopeptide Bj‐PRO‐7a in spontaneously hypertensive rats. (5th September 2021) - de Jesus, Érika Fernandes; Nunes, Allancer Divino de Carvalho; Pontes, Carolina Nobre Ribeiro; Macedo, Larissa Matuda; Mendes, Elizabeth Pereira; Ianzer, Danielle Alves; da Costa, Michael; Ghedini, Paulo César; dos Santos, Fernanda Cristina Alcantara; Biancardi, Manoel Francisco; Castro, Carlos Henrique
Abstract: The proline‐rich oligopeptide from Bothrops jararaca snake venom, Bj ‐PRO‐7a, promotes acute effects in blood pressure in hypertensive animals. However, the cardiac effects of this heptapeptide are completely unknown. Thus, we sought to evaluate whether the Bj ‐PRO‐7a could protect against cardiac remodelling in spontaneously hypertensive rats (SHR). SHR were treated with Bj ‐PRO‐7a (71 nmol/kg/day, s.c.) or saline for 28 days. Wistar rats were used as control. Systolic blood pressure (SBP) and heart rate (HR) were measured by tail‐cuff plethysmography. Cardiomyocyte diameter and interstitial and perivascular fibrosis of the left ventricle (LV) were evaluated using Picrosirius staining. Immunofluorescence was used to detect collagen I and III. Fibroblast proliferation was assessed by immunohistochemistry to detect proliferating cell nuclear antigen (PCNA). Protein expression was assessed by western blot. The superoxide dismutase and catalase activities and the concentration of lipid peroxidation products were evaluated in the LV. The SBP and HR were not different between treated and non‐treated SHR at the end of the treatment. However, Bj ‐PRO‐7a attenuated the cardiomyocyte hypertrophy, deposition of interstitial and perivascular fibrosis and collagen I, and positive PCNA‐labelled fibroblasts. This peptide also reduced the increased levels of TBARS, expression and activity of catalase, and activity of SOD in LV from SHR. Also, the Bj ‐PRO‐7a increased the expression of metalloproteinases‐2 in SHR hearts. These findings demonstrate that the Bj ‐PRO‐7a reduced the pathological cardiac remodelling in a pressure‐independent manner in hypertensive rats through mechanisms mediated by oxidative stress regulation.